Effect on the performance and emissions of methanol/diesel dual-fuel engine with different methanol injection positions. (1st January 2022) - Xu, Changchun; Zhuang, Yuan; Qian, Yejian; Cho, Haengmuk
Highlights: Study the effect of methanol injection position on engine combustion and emissions. Pre-intercooler injection reduces ignition delay and reduces HC and CO emissions. Post-intercooler injection, HC and CO emissions are reduced at medium and high loads. The intake manifold injection reduces the in-cylinder pressure and NOx emissions. Abstract: In methanol/diesel combined injection mode engines, the high latent heat of vaporization of methanol reduces the combustion temperature. It effectively reduced NOx emissions, which led to the deterioration of combustion under high blending ratio conditions. This study attempted to improve the adverse effect of high latent heat vaporization on combustion by changing the methanol injection positions. The experiment was carried out on a Yunnei D30 inline 4-cylinder turbocharged and intercooled common rail diesel engine. Methanol that used five kinds of methanol substitution rates (0%, 10%, 20%, 30%, 40%) was injected at three positions, namely pre-intercooler, post-intercooler, and intake manifold under three load conditions (100 N.m, 200 N.m, 300 N.m) with four engine speeds of 1200 rpm, 1400 rpm, 1800 rpm and 2000 rpm, respectively. The results showed that under medium and low load conditions, regardless of the injection position, the methanol substitution rate increased, the maximum explosion pressure in the cylinder decreased, the peak heat release rate shifted backward, the ignition delay prolonged, and total energy consumption increased, HC and CO emissions increased, and NOx emissions reduced. Under high load conditions, with the methanol substitution rate increasing, maximum explosion pressure first increased and then decreased. The total energy consumption first decreased and then increased, while the HC and CO emissions slightly increased and the NOx emissions decreased. Under medium and low load conditions, varying methanol injection positions could lessen the adverse effects of methanol blending combustion. Methanol injected into the pre-intercooler, which utilized the high temperature of intake air after pressurization, vaporized effectively, shortened ignition delay and combustion duration, and reduced HC and CO emissions. At post-intercooler, HC emissions slightly increased under low load conditions, ignition delay was shortened under medium load conditions, and cylinder pressure was restored to the level of pure diesel. Under high-speed and high-load conditions, due to higher cylinder temperature, HC and CO emissions decreased, and NOx emissions increased. At the intake manifold, the lowest in-cylinder pressure and slowest heat release rate were found at low-load conditions, but NOx emissions were reduced the most at high speed and high load conditions.